The Characterization of God and Jesus in the Apocalypse: A Narrative Critical Approach - Frayne, Eileen L. (My University, 1995)
This thesis is an attempt to discover something of the theology and chrlstology of the author of the Apocalypse through a study of his characterizations of God and Jesus. The methodology of Narrative Criticism is used, particularly with respect to the literary techniques of characterization. Once established these are applied to carefully selected pericopes throughout the text.
The titles he ascribes to them are the first topic for analysis, for, clearly, they convey a great deal about their perceived characters and statuses. The author describes thelr respective appearances in his visions--not in a matter-of-fact way, but using symbols drawn mostly from the Hebrew Bible, which would have been familiar and full of meaning for his readers/listeners.
The question must be asked, is it appropriate to apply narrative criticism to something as ethereal as a series of 'visions', which may be either genuine and historical, or literary fictions such as are typical of many Jewish apocalypses? Whether or not the visions are 'genuine' is largely immaterial, since the seer of Patmos embedded them in a narrative framework, which legitimates the use of this methodology.
Other writers on this topic may have chosen different pericopes as being more illustrative of the characters of God and Jesus, but those which I have selected, I believe, together create the clearest portraits of the two divine Dramatis Personae in 'John's' Revelation. It has been my concern that the author's own conceptions of the characters of God and Christ should emerge from this study--and t hey have done so--c ast, apparently, in the mold of the powerful Shepherd/Kings who, for almost three millennia, terrorized the peoples of the Ancient Near Eastern world
Biblical quotations are from the NSRV except where otherwise specified.
Keywords: Religion; Religion